KAJIAN HUKUM TERKAIT PENYELESAIAN TERBITNYA SERTIPIKAT TANPA SEPENGETAHUAN PIHAK YANG MENGUASAI TANAH - Cahyaningtyas, Kartika; Ali, Muh. Isra Bil (LPPM institut Teknologi Bisnis AAS Indonesia, 2023)
This research examines and analyzes the resolution of cases related to the issuance of certificates without the knowledge of the party controlling the land because certificates can provide a guarantee of legal certainty. Legal certainty is included in legal protection so that it is not treated arbitrarily, which means that someone will be able to obtain something that is expected in certain circumstances, other things that are obtained with the aim of order in society. The method used is normative research with a problem approach, namely statutory and case approaches. The results of the research are that litigation is needed to resolve this because Indonesia adheres to a negative publication system with a positive tendency where the state guarantees the registration of a certificate but can still be sued if the data guaranteed by the state is not correct. Legal measures taken through the courts include the Administrative Court or District Court. This is because the person who registers the land does not control the land and without permission from the person who controls the land, this results in losses for those who control the land. Keywords: Land Registration, Legal Certainty, Legal Remedies